The evolution of Wisconsin's woody biofuel policy: Policy layering and dismantling through dilution. (September 2020) - Barnett, Brad; Wellstead, Adam M.; Howlett, Michael
Abstract: This paper examines the intersection between changing goals, actors and institutions in designing Wisconsin's woody biopower policy mix. Using a historical institutionalist analysis over three decades (1990–2020) of Wisconsin energy and forest products policy development, changes in the capacity of the mix to encourage the production of forest biopower are examined. The study reveals the state experienced early periods of policy congruency via policy layering as efforts to promote the use of forest waste as biofuel emerged as an important part of the state's overall energy mix. However, more recent calls for cost effective and affordable energy has resulted in "policy dilution" in this sector, a form of policy dismantling largely ignored in the literature on the subject. This story is one like policy 'stretching' in which a policy mix develops through patches and layering until such time as its internal contradictions drive processes of more substantive reform. Although the policy change literature tends to focus on cases in which reforms are added to mixes in order to strengthen a stretched regime, as this case study shows, this process can also work in reverse, with additions paradoxically leading to the dismantling of important aspects of an existing policy arrangement.